Pa'belle Fishermen Empowerment: A Communicative Action Perspective in An Industrialized Society - Ismail, Ince Rahma; Idris, Rabihatun; Kesuma, Andi Ima (Fakultas Sastra - Universitas Muslim Indonesia, 2023)
This research examines the empowerment process of Pa'belle fishermen from a communicative action perspective, recognizing that all their activities serve as communication tools with meaning and messages for others. The study aims to analyze the problems faced by the fishermen during the empowerment process, as well as the communicative actions they undertake and the direction of their empowerment. The research utilizes a qualitative Single Case Study approach, with 15 purposively selected fishermen as informants who have at least two years of experience working as fishermen and understand the challenges experienced by fishermen and fishermen groups. Data collection involved in-depth interviews, participant observation, and literature study, while data analysis employed a three-step technique of data categorization, data reduction, and conclusion drawing. The study findings revealed various problems faced by Pa'belle fishermen in the empowerment process, including challenges with government support such as DAU 2021 assistance, the need for